Exploring the Use of Communication as a Tool for Effective Government’s Revenue Mobilization: A Case of Adentan Municipal Assembly - Manu, Kyei (UniMAC-GIJ, 2020)
Local government administration over the years existed to ensure good governance at the local level and to facilitate improvement in the quality of life of the people through the provision of equitable social amenities and projects to guarantee a total development of its community. However, to be able to achieve such development programs, revenue mobilizations at the local assemblies are deemed very essential to the survival and uninterrupted operations of the Municipal and District Assemblies. But as the years gone by, effective revenue mobilization has been the bane for most municipal and district assemblies in Ghana, and Adentan municipal assembly is therefore not an exception to the import of topic this research seeks to address. Meanwhile, little attention over the period has been accorded to the importance of communication by local assembly authorities as an effective tool to improve local government revenues. In addition, prior research on revenue mobilization has predominantly focused on some historical antecedents of mobilizing revenues and other related issues such as local assembly’s over reliance on central government to support its revenue capabilities. Most of the research to some extent did not concentrate much on emerging and modern approaches (eg communications) that can help to improve revenue mobilization at the local level. This study on the other hand tends to dwell on exploring the use of communication as a tool for an effective government revenue mobilization at the local assembly level specifically in the Adentan Municipal Assembly, taking into consideration the necessity of communication to modern day governance and how the various communication strategies and approaches can be utilize to effectively improve local government revenues. The research also makes appropriate and relevant recommendations deemed vital to the area of study based on the findings of the research to help achieve the aim of the study and provide conclusions to that effect.
MA Development Communication
Keywords: Communication, Government’s Revenue Mobilization, Adentan Municipal Assembly, Ghana, Accra